Penerapkan Model Pembelajaran Berbasis Karakter Pada Pendidikan Jasmani Kepada Guru-Guru Pendidikan Jasmani Se-Kuantan Singingi - Dupri Dupri; Oki Candra; Novia Nazirun; Merlina Sari (UIR Press, 2019)
This activity aims to provide training to physical education teachers in Kuantan Singingi district in the application of the character-based Jasamani education learning model when learning physical education in schools. So that the implementation of the K13 curriculum in schools goes well and the role of a physical education teacher in the future will be in handling the character of students to be better and to educate people who have the character of the qarimah. Activities include training in the application of physical education learning models to physical education teachers in Kuantan Regency. This activity was carried out at SMA N Pintar of Kuantan Bay, Kuantan Singingi Regency. The activity was attended by 35 high school level physical education teachers who are equal in the Kuantan Singingi Kabutapan. The results of this activity are very good because it is very helpful to the knowledge of high school physical education teachers in the application of learning models that must be realized in the K13 curriculum.